TRADITIONAL RECREATIONAL GAMES IN THE EARLY GRADES OF ELEMENTARY SCHOOL - Castro de Matos, Cristiano (Revista Gênero e Interdisciplinaridade, 2023)
The object of this article are traditional recreational games based on popular culture that are taught by elders across generations establishing the concept of these games and demonstrating their importance in physical education classes. It also highlight the relationship between student-teacher and how developing children are part of the construction of their identity related to the family and school environment. Aspects related to the use of traditional recreational games in Physical Education and their importance were also analyzed.